Determinants of Curly Chili Demand in Ambon City - Desry J. Louhenapessy; Ummi Duwila; Andre Sapthu; Selvenco Tuasuun; Jani; Fredy H. Louhenapessy; Fibryano Saptenno (ARRUS Journal of Social Sciences and Humanities, 2024)
This study aims to analyze the influence of curly chili prices, household income, and the number of household dependents on the demand for curly chilies in Ambon City using the multiple linear regression method. Primary data was collected through a survey of 300 households in Ambon City, with the dependent variable being the monthly purchase quantity of curly chilies, while the independent variables include the price of curly chilies, household income, and the number of dependents. The analysis results show that the price of curly chilies has a significant negative effect on demand, with an increase in price leading to a decrease in purchase quantity. Additionally, household income and the number of dependents also have a significant impact, where an increase in income and the number of dependents boosts demand. These results indicate the existence of complex interactions between these factors in shaping the demand for curly chilies in Ambon City, which need to be considered in policy planning and marketing strategies to maintain market stability and meet consumer needs.